2015
DOI: 10.1039/c5an01964h
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical signatures of multivitamin mixtures

Abstract: Distinct electrochemical signatures of multivitamins using cyclic square wave voltammetry at a disposable screen printed electrode.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…Most focused on electroanalysis. [28][29][30] Webster wrote an excellent review of lipid soluble vitamin electrochemistry based on careful voltammetric studies from his group. 31 Biochemistry of vitamins is well reviewed in Reference 32.…”
Section: G26mentioning
confidence: 99%
“…Most focused on electroanalysis. [28][29][30] Webster wrote an excellent review of lipid soluble vitamin electrochemistry based on careful voltammetric studies from his group. 31 Biochemistry of vitamins is well reviewed in Reference 32.…”
Section: G26mentioning
confidence: 99%
“…Between all these vitamins, only B 5 seems electrochemically inactive in the potential ranges usually achievable at conventional electrodes. It was shown that it is not detectable at some electrode/supporting electrolyte systems, since no peaks were evidenced in the corresponding voltammograms . Only one paper deals with the redox behavior of the alcohol derivative, D‐panthenol .…”
Section: Water Soluble Vitaminsmentioning
confidence: 99%
“…A large number of electrochemical techniques have been proposed for the determination of individual vitamins, while their simultaneous determination in mixtures is more limited. In fact, only one paper to date was proposed for determining more than three vitamins simultaneously . Moreover, it was frequently reported the necessity of performing complex calibration procedures when the quantification of several vitamins is needed .…”
Section: Introductionmentioning
confidence: 99%
“…Cyclic square‐wave voltammetry has been employed here to demonstrate such selective EP and NE measurements. Such C‐SWV operation combines oxidative and reductive square‐wave voltammetric scans in a cyclic manner to offer qualitative and quantitative information on micromolar concentrations of electroactive species . Both the oxidation and reduction peaks of micromolar levels of target molecules are thus recorded rapidly.…”
Section: Introductionmentioning
confidence: 99%
“…Both the oxidation and reduction peaks of micromolar levels of target molecules are thus recorded rapidly. C‐SWV has been shown recently to be effective to provide distinct electrochemical fingerprints of gunshot residues to multi‐vitamins in complex mixtures. By presenting oxidation and reduction behavior through C‐SWV, the redox behavior of electroactive molecules can be analyzed in a manner analogous to cyclic voltammetry.…”
Section: Introductionmentioning
confidence: 99%